Sistem Informasi Penjualan Tiket Pesawat Pada PT. Pesona Sumatera Holidays Menggunakan Metode Prototype - Sari, Putri Permata (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2020)
PT. Pesona Sumatera Holidays is a company that provides transportation services and flight ticket sales services for all airlines. In making flight ticket sales reports at the company still using the manual method, this causes a buildup of paper, so it is very difficult to find the required documents. For this reason, the writer provides a solution by designing and building a flight ticket sales information system at PT. Pesona Sumatera Holidays, where all customer data will be inputted and stored in a computerized manner so that it can help the process of making financial reports more effectively and efficiently as expected by its users. The design of this flight ticket sales information system uses a prototype method with visual studio 2015 program language equipped with SQL Server 2008 database. The flight ticket sales information system is expected to simplify the process of making flight ticket sales reports at PT. Enchantment of Sumatra Holidays.